1982
DOI: 10.2466/pms.1982.55.2.479
|View full text |Cite
|
Sign up to set email alerts
|

Reactions to Men and Women Who Cry: A Study of Sex Differences in Perceived Societal Attitudes versus Personal Attitudes

Abstract: This study examined sex differences and similarities in sex-role attitudes using reactions to males' and females' crying as the stimulus situation. 285 male and 307 female students completed questionnaires. Subjects were asked to indicate their reactions to the sight of a woman crying and to the sight of a man crying. They were also asked to indicate how they thought “people” react to the sight of a man or a woman crying. Subjects perceived “people” as holding a double standard of crying, with much greater acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 8 publications
1
30
1
Order By: Relevance
“…Cornelius and colleagues (Cornelius & Lubliner, 2003;Cornelius et al, 2000) and Hendriks and Vingerhoets (2006) found that neither the sex of the respondent nor that of the crying person substantially influenced social reactions to crying. However, Cretser, Lombardo, Lombardo, and Mathis (1982) and Jesser (1989) found that (a) participants in their studies were more inclined to sympathize with and provide comfort and help to a crying woman than a crying man and (b) female participants responded more favorably to a crying person than did male participants. Labott et al's (1991) results also indicated sex differences, but in the opposite direction: Respondents liked men more when they cried, whereas they like women more when they displayed no emotional reaction to stimuli.…”
Section: Sex Differences In Reactions To Cryingmentioning
confidence: 96%
“…Cornelius and colleagues (Cornelius & Lubliner, 2003;Cornelius et al, 2000) and Hendriks and Vingerhoets (2006) found that neither the sex of the respondent nor that of the crying person substantially influenced social reactions to crying. However, Cretser, Lombardo, Lombardo, and Mathis (1982) and Jesser (1989) found that (a) participants in their studies were more inclined to sympathize with and provide comfort and help to a crying woman than a crying man and (b) female participants responded more favorably to a crying person than did male participants. Labott et al's (1991) results also indicated sex differences, but in the opposite direction: Respondents liked men more when they cried, whereas they like women more when they displayed no emotional reaction to stimuli.…”
Section: Sex Differences In Reactions To Cryingmentioning
confidence: 96%
“…There is evidence that expectations likely will differ, as researchers have found different expectations for emotionality in males and females (see, e.g., Broverman, Vogel, Broverman, Clarkson, & Rosenkrantz, 1972). Earlier researchers generally found that crying from females was seen as more acceptable (see, e.g., Cretser, Lombardo, Lombardo, & Mathis, 1982), although there is recent research to suggest that perceptions of male criers may be changing (Labott, Martin, Eason, & Berkey, 1991; for a review see Warner & Shields, 2007). In any case, researchers should not assume that results will be the same for both genders.…”
Section: Future Researchmentioning
confidence: 99%
“…Respondents were more inclined to comfort and help a crying woman than a crying man (Cretser, Lombardo, Lombardo, & Mathis, 1982;Jesser, 1989). A crying man was more likely to be helped by female than by male respondents and was more looked down on by male than by female respondents (Cretser et al, 1982).…”
Section: Social Reactions To Cryingmentioning
confidence: 99%
“…Respondents were more inclined to comfort and help a crying woman than a crying man (Cretser, Lombardo, Lombardo, & Mathis, 1982;Jesser, 1989). A crying man was more likely to be helped by female than by male respondents and was more looked down on by male than by female respondents (Cretser et al, 1982). In contrast, in the studies of Cornelius and colleagues (Cornelius and Lubliner, 2003;Cornelius, Nussbaum, Warner, & Moeller, 2000) and of Hendriks and colleagues (Hendriks & Vingerhoets, 2006;Hendriks, Croon, et al, in press), the sex of the respondent and of the crying person did not substantially influence the social reactions to crying.…”
Section: Social Reactions To Cryingmentioning
confidence: 99%
See 1 more Smart Citation